Controlling the magnetic properties of two-dimensional carbon-based Kagome polymers. (April 2022) - Anindya, Khalid N.; Rochefort, Alain
Abstract: With the help of first principles calculations, we have explored a promising route to control the magnetic properties of two-dimensional organic polymers based on all-carbon triangulene monomers. Similar to small triangulene nanostructures, the Kagome-organized triangulene polymer exhibits an antiferromagnetic ground state, but behaves as a Mott-insulator with relatively poor carrier mobilities. The doping of triangulenes with boron or nitrogen atoms contributes to switch the ground state of the polymer into a stable ferromagnetic phase, well separated in energy from the antiferromagnetic phase. The existence of a stable ferromagnetic phase is a direct consequence of electron confinement within B/N-rich triangulenes, where the D 3 h symmetry of the monomers in the Kagome pattern plays a major role on the resulting electronic structure properties. In addition, the two-dimensional Kagome lattice arrangement of B-rich triangulene polymer leads to highly dispersed spin-polarized semiconducting bands and high carrier mobilities that largely exceed known values for pure silicon. In contrast, the ferromagnetic phase of N-rich polymer shows half-metallic behaviour with lower mobilities than B-rich cases. Our results suggest that triangulene-based polymers could be used in diverse sectors from spin-based logic devices to quantum storage applications.